Theoretical and Experimental Analysis on Thermal Properties of Flexible Thermal Insulation Composite Fabric (Journal of Fiber Bioengineering and Informatics, 2008)
In this paper, the theoretical heat transfer of flexible thermal insulation composite fabric hasbeen analyzed and the designing method has been discussed in systematically. Heat transfer analysisof flexible thermal insulation composite fabric is sometimes too complex to be used in practicaldesign application. So, it is necessary to have simpler methods to evaluate the heat transfer fluxthrough multilayer thermal insulation. The paper presented experimental and theoretical studies on thedetermination of the effective thermal conductivities of the flexible thermal insulation composite fabric.A mathematical model has been developed to describe the heat flux through the composite fabric,where the heat transfer consists of thermal radiation, solid spacer and residual gas conduction. Thethree distinct heat transfer modes are treated as parallel thermal resistances, and the multilayer thermalinsulation behaviour considering a layer-to-layer approach and is based on an electrical analogy. Then,thermal performances of flexible thermal insulation composite fabric are presented, selecting differentmaterials, different layers and different spacers. Finally, the prime structure of the flexible thermalinsulation composite fabric is obtained through the theoretical and experimental analysis.
Keywords: flexible; composite fabric; mathematical model; thermal properties